A literature review on the student evaluation of teaching: An examination of the search, experience, and credence qualities of SET. Issue 2 (6th December 2018) - Ching, Gregory
Abstract : Purpose: Competition among higher education institutions has pushed universities to expand their competitive advantages. Based on the assumption that the core functions of universities are academic, understanding the teaching–learning process with the help of student evaluation of teaching (SET) would seem to be a logical solution in increasing competitiveness. The paper aims to discuss these issues. Design/methodology/approach: The current paper presents a narrative literature review examining how SETs work within the concept of service marketing, focusing specifically on the search, experience, and credence qualities of the provider. A review of the various factors that affect the collection of SETs is also included. Findings: Relevant findings show the influence of students' prior expectations on SET ratings. Therefore, teachers are advised to establish a psychological contract with the students at the start of the semester. Such an agreement should be negotiated, setting out the potential benefits of undertaking the course and a clear definition of acceptable performance within the class. Moreover, connections should be made between courses and subjects in order to provide an overall view of the entire program together with future career pathways. Originality/value: Given the complex factors affecting SETs and the antecedents involved, there appears to be no single perfect tool to adequately reflect what is happening in the classroom. As different SETs may be needed for different courses and subjects, options such as faculty self-evaluation and peer-evaluation might be considered to augment current SETs.